Move Analysis of Review Article Abstracts: Variations and Commonalities in Two Health Science Subdisciplines - Villia, Ade Sissca; Arono; Sumaryono, Dino; Suryanti, Reny (UNIB Press, 2024)
Over the past few years, genre studies in research article abstracts have prompted the interest of numerous researchers. However, the scope of genre analysis in studying the abstracts of review articles is highly restricted. Thus, offering a structured framework as guidelines for the writers can serve as a resolution to the issue. The objective of this study is to examine the composition of abstracts in review articles within the fields of health information and nursing. To this end, a total of 100 abstracts were chosen from articles published in prestigious international journals. The present study utilised Soy, Arsyad, and Syafryadin’s (2023) five-move model. A slight modification was introduced in the present study by including the Result move separated from the Discussion move. The results identified six moves: Background, Objective, Method, Result, Discussion, and Conclusion. The method move (M3) was obligatory in nursing, while the objective move (M2) was obligatory in health information. Then, Background-Objective-Method-Result-Conclusion was the most frequent sequence in the two subdisciplines. As a practical implication, novice writers might consider using the fundamental principle of rhetorical move structure while writing an abstract for a review article. The present study can potentially serve as a basis for further studies.